ADHD Rehabilitation through Video Gaming: A Systematic Review Using PRISMA Guidelines of the Current Findings and the Associated Risk of Bias - Strahler Rivero, Thiago; Herrera Nuñez, Lina Maria; Uehara Pires, Emmy; Amodeo Bueno, Orlando Francisco (Frontiers in Psychiatry, 2015)
Empirical research studies have highlighted the need to investigate whether video game can be useful as a tool within a neuropsychological rehabilitation program for Attention Deficit Hyperactivity Disorder patients. However, little is known about the possible gains that this kind of video game based interventions can produce and even if these gains can be transferred to real life abilities. The present paper aims to uncover key information related to the use of video game in ADHD neuropsychological rehabilitation/intervention by focusing on its gains and its capability to transfer/generalize these gains to real life situation via a systematic review of the empirical literature. The PRISMA guidelines were adopted. Internet-based bibliographic searches were conducted via seven major electronic databases (i.e., PsycARTICLES, PsycINFO, Web of Science, Core Collection BIOSIS Citation Index, MEDLINE, SciELO Citation Index, and PubMed) to access studies examining the association between video game interventions in ADHD patients and behavioral and cognitive outcomes. A total of 14 empirical studies meeting the inclusion criteria were identified. The studies reported the attention, working memory and the behavioral aspects as the main target of the intervention. Cognitive and behavioral gains were reported after the video game training. However, many bias related to the choice of outcome instruments, sampling and blindness of assessors, weaken the results power. Additional researches are important to clarify the effects and stability of the video games training programs, and an important effort should be made to construct better methods to assess improvements on everyday cognitive abilities and real world functioning.